Evidence-Based Reasoning: Evaluating Daily Experiences in the Engineering Design Classroom for Middle School Students - Putra, P. D. A.; Yusmar, F.; Kasah, I. J.; Handayani, R. D.; Fadzil, H. M. M. (Jurnal Pendidikan IPA Indonesia, 2024)
Effective argumentation in science classrooms relies on the ability of students to evaluate evidence. However, there is a gap in research concerning students’ capacity to validate evidence, particularly in the context of engineering design. Evidence validation skill is crucial for fostering reasoning and strengthening argumentation. This study aimed to explore students’ ability to investigate evidence in engineering design classrooms, drawing from their daily life experiences. This study was framed by a qualitative approach, with a case study design involving students in a coffee farming community. The students were assigned an engineering project related to coffee preparation, based on a problem statement devised by their teachers using the Engineering Design Process. Data was collected through observation of the students’ activities in the engineering classroom. Small-group discussions were held, and the data was recorded, transcribed, and analyzed using semantic gravity (SG). Our results reveal that students hailing from farming backgrounds were able to devise solutions based on their firsthand experiences in processing coffee with their families. The environment in which the students were raised plays a pivotal role in their learning. These findings underscore the importance of contextual learning in educational design. Educators should consider students’ backgrounds and experiences when planning instructional strategies.